Knowledge and Practice of Breast Self-Examination among Women in Seberang Perai Utara District, Penang: AMDI Medical Coach Experience - Law, Kim Sooi; Musa, Muhamad Yusri; Omar, Eshaifol Azam; A. Karim, Noor Khairiah; Hami, Rohayu (2015)
Breast cancer is the leading cause of cancer mortality in women and is a major health concern in both developing and developed countries 1. Regular breast cancer screening is the single most important public health strategy to reduce breast cancer mortality 2. Breast self-examination (BSE) is one of the screening modality available and regular BSE is the best way to notice breast changes. Women should be encouraged to know what is normal for them, be informed of early symptoms of breast cancer, and promptly report any changes or concerns 3. Advanced Medical and Dental Institute (AMDI) Medical Coach begins its operation in 2013 with the aim to create awareness among the public about the importance of health screening which include BSE and mobile mammography